Asparagine Synthetase Expression and Phase I Study With L-Asparaginase Encapsulated in Red Blood Cells in Patients With Pancreatic Adenocarcinoma. Issue 7 (October 2015) - Bachet, Jean-Baptiste; Gay, Fabien; Maréchal, Raphaël; Galais, Marie-Pierre; Adenis, Antoine; MsC, David Salako; Cros, Jerome; Demetter, Pieter; Svrcek, Magali; Bardier-Dupas, Armelle; Emile, Jean-François; Hammel, Pascal; et al.
<x xml:space="preserve">Abstract</x> Objectives Asparaginase encapsulated in erythrocytes (ERY-ASP) is a potentially effective drug in patients with pancreatic adenocarcinoma (PAC) with null/low asparagine synthetase (ASNS) expression. Our aims were to assess ASNS expression in PAC from a large cohort and its prognostic and/or predictive value and to conduct a phase I trial with ERY-ASP in patients with metastatic PAC. Methods Asparagine synthetase expression was evaluated using immunohistochemistry in resected PAC (471 patients) and in pairs of primary tumor and metastases (55 patients). Twelve patients were included in the phase I trial and received a single administration of ERY-ASP (25-150 IU/kg). Results Null/low ASNS expression was found in 79.4% of the resected PAC with a high concordance between primary tumor and metastases. Asparagine synthetase expression was significantly correlated with sex and CXCR4 expression. In the phase I trial, ERY-ASP was well tolerated by patients with metastatic PAC. No patient had DLTs, and 6 patients had at least 1 ERY-ASP causally related adverse event out of the 12 adverse events reported. Conclusions Given the high rate of PAC with null/low ASNS expression and the good tolerability profile of ERY-ASP, ERY-ASP should be evaluated in further clinical studies in metastatic PAC.